Investigating the Amount and Goals of Using Social Networks Among Students of Bamyan University: A Historical Analysis - Akbari, Najibullah; Samimi, Shirali (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
The study of social networks, which have been around for a relatively short time, is a topic of interest to many students and researchers. The use of these emerging networks spans a wide spectrum from personal relationships to global relationships. This phenomenon has become a full-fledged subject in social and media research. The present study aims to investigate the extent and purposes of using social networks among students of Bamyan University. The research method is descriptive and survey-based. The statistical population of the study is made up of students of Bamyan University, and from the statistical population of 8,100, 367 people were selected as a statistical sample. The researcher created a questionnaire as a data collection tool. The research findings showed that 36.5 percent of Bamyan University students use social networks to a large extent. The results also show that 32.7% of them always use social networks to communicate with their family, 17.2% always use them for entertainment and fun, and 33% use them to follow vacancies and find jobs. According to the statistics, we can say that the main purposes of students using social networks are: Spending time and entertainment, keeping in touch with family and friends, finding a job, and registering for vacancies are among the goals of social media users among Bamyan University students. In addition to the aforementioned goals, secondary uses such as keeping in touch with the university, finding scholarships, getting informed about news, staying up to date, and being featured are also among the goals of social media users among Bamyan University students. In addition, it was found that there is a relationship between the variables of the amount of use and the purposes of using social networks, and the gender and marital status of students.